2003
DOI: 10.1046/j.1467-2494.2003.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre comparison of skin hydration in terms of physical‐, physiological‐ and product‐dependent parameters by the capacitive method (Corneometer CM 825)

Abstract: A multicentre study for measuring skin hydration with 349 volunteers was carried out in six different laboratories. The purpose of the study was to investigate physical-, physiological- and product-dependent parameters of three test emulsions (base, base + moisturizer and base + moisturizer + lipids) in a double-blind study. A comparison between analogous and digital sensor technology of the Corneometer CM825 was examined. Here, a clear relationship between both sensor types could be highlighted. A vital point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(158 citation statements)
references
References 9 publications
6
141
0
3
Order By: Relevance
“…The improvement in skin moisturising was statistically significant at the abdominal skin application site. The results of the present study are consistent with the literature data [37][38][39][40][44][45][46][47][48]. In particular, the results are consistent with those of Li et al [44], who also showed that the measures taken one hour of the application are predictive of the stratum corneum moisturising obtained after a multiple applications for one or 2 weeks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The improvement in skin moisturising was statistically significant at the abdominal skin application site. The results of the present study are consistent with the literature data [37][38][39][40][44][45][46][47][48]. In particular, the results are consistent with those of Li et al [44], who also showed that the measures taken one hour of the application are predictive of the stratum corneum moisturising obtained after a multiple applications for one or 2 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…It is regarded as a reliable measure of skin conditions and also this method gained validity and use diffusion in dermatology and cosmetics [37][38][39]. The reliability and the reproducibility of these measures were previously demonstrated [40][41][42].…”
Section: Methodsmentioning
confidence: 99%
“…are typically associated with normal skin. Thus, an increase in corneometry values mirrors a skin-moisturizing effect (17).…”
Section: Subjects and Assessmentsmentioning
confidence: 99%
“…A Corneometer® CM 825 was used to measure the hydration level in five locations to obtain average values. The Corneometer® is based on a capacitance measurement and has a measurement depth of 10-20 µm [25]. For human skin, measuring the capacitance effectively provides an indirect measurement of the water content of the stratum corneum.…”
Section: Skin Preparationmentioning
confidence: 99%